PENGARUH TERPAAN SALES PROMOTION DARI SALES CALL DAN KUALITAS KOMUNIKASI FRONT OFFICE TERHADAP LOYALITAS KONSUMEN ARTOTEL GAJAHMADA-SEMARANG - Marshanda Putri, Tyara; Naryoso, agus; Pradekso, Tandiyo (Interaksi Online, 2024)
This study aims to investigate the influence of sales promotion exposure from sales calls and front office communication quality on consumer loyalty at ARTOTEL Gajahmada-Semarang. The study employs an explanatory quantitative method with purposive sampling involving 100 respondents. Simple linear regression analysis is used for data analysis. The research findings indicate that sales promotion exposure from sales calls significantly influences consumer loyalty at ARTOTEL Gajahmada-Semarang, with a significance level of 0.036 < 0.05, although the R Square value suggests a weak influence (0.044). Similarly, front office communication quality significantly affects consumer loyalty at ARTOTEL GajahmadaSemarang, with a significance level of 0.028 < 0.05, but the R Square value indicates a weak influence (0.048). The weak influence may be attributed to inadequate human resources, as the staff at ARTOTEL Gajahmada-Semarang may not be sufficient to handle all staying guests effectively.